Arithmatical consequences of two identities of B. Gordon - John A. Ewell (International Journal of Mathematics and Mathematical Sciences)
From two partition identities of Basil Gordon the author derives two recursive formulas for the sum-of-divisors function. A third application yields an alternate proof of Rmanujan's theorem on the divisibility of certain values of the partition function by the modulus 5.